Integrated Blood Multiparameter Precise Sensing System for Economical, Rapid, and Accurate Detection of Blood Biochemical Indicators: From Centrifugation to Sensing - Chen, Yiyin; Yang, Chengduan; Yang, Cheng; Liu, Ziqi; Kao, Hsiaohan; Chen, Hui-Jiuan; Tang, Pei (ACS omega, 2025)
Blood is enriched with physiological information and could provide valuable references for the diagnosis of various diseases. Influenced by a few factors, including glycolysis, the direct testing of blood may lead to biased results. Healthcare facilities routinely eliminate this bias by centrifugation. However, conventional centrifuges and analysis equipment are large and electricity dependent, limiting their application in less-developed regions. In this work, an integrated blood multiparameter precise sensing system (BMPSS), consisting of a portable manual centrifuge (PMC) and three flex sensor patches (FSPs), was developed for rapid manual centrifugation of blood and detection of glucose, cholesterol, and uric acid levels in postcentrifugation plasma. The test results in solution illustrated that FSPs have favorable linear responsiveness, reproducibility, temporal stability, and selectivity. Experimental results based on rat blood indicated that the PMC has centrifugation results similar to those of commercial centrifuges, and the BMPSS enables adequate centrifugation and precise detection of blood, leading to indications of a wide range of diseases. The results conclusively point to the potential clinical applicability of BMPSS. This work presents the first system that achieves low-cost, portable, electricity-free centrifugation and in situ rapid sample testing; we believe it has promising applications in harsh environments.